Long-term Outcomes of Gastroenteropancreatic Neuroendocrine Tumors. Issue 3 (March 2018) - Chi, Weiwei; Warner, Richard R.P.; Chan, David L.; Singh, Simron; Segelov, Eva; Strosberg, Jonathan; Wisnivesky, Juan; Kim, Michelle K.
Abstract : Objectives: Gastroenteropancreatic neuroendocrine tumors (GEP-NETs) are rare but have been increasing in incidence. Limited data on the long-term outcomes of patients with these tumors are available. Methods: In this study, we used population-based data from the National Cancer Institute to assess long-term disease-specific survival (DSS) of patients who have undergone surgery for nonmetastatic disease. All patients with NETs of the stomach, small intestine, colon, rectum, appendix, and pancreas diagnosed between 1988 and 2009 were identified from the Surveillance, Epidemiology and End Results registry. Staging was derived from Surveillance, Epidemiology and End Results data using the European Neuroendocrine Tumor Society guidelines. Cases with incomplete staging data were excluded, along with those with stage IV disease, or those who did not undergo surgical resection. Results: Kaplan-Meier analyses were constructed to determine DSS. Analyses were further stratified according to tumor site, stage at diagnosis, and tumor grade. Overall, 13, 348 patients with GEP-NETs meeting the inclusion criteria were identified. Conclusions: There were excellent outcomes for most GEP-NET patients, with a 20-year DSS of greater than 75% across all sites and stages. Pancreatic tumors had the worst outcomes, but DSS remains greater than 50% at 20 years.